Los poderes feudales. Las maneras de la extracción del excedente en la economía medieval - Domínguez González, David Jorge (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
This article wants to settle down a political understanding of mechanism underlying the extraction of surplus in a medieval economy. Also, we place such mechanism at the level of a reality that is not strictly economic, because they include elements that cannot be reduced to a contractual or economist arrangement. From this point of view, the institution of vassal no longer seems a prerogative prior to the subsequent centralization of power, capable ultimately of move transferring the vassal’s bond toward the superior power, but rather the centralization acts in the sense of deviating loyalty of the men from the lower ranks, which didn’t lend direct fidelity to the king but to its more immediate lords.